Therapeutic efficacy of an Ad26/MVA vaccine with SIV gp140 protein and vesatolimod in ART-suppressed rhesus macaques - John D. Ventura; Joseph P. Nkolola; Abishek Chandrashekar; Erica N. Borducchi; Jinyan Liu; Noe B. Mercado; David L. Hope; Victoria M. Giffin; Katherine McMahan; Romas Geleziunas; Jeffrey P. Murry; Yunling Yang; et al. (npj Vaccines, 2022)
Abstract Developing an intervention that results in virologic control following discontinuation of antiretroviral therapy (ART) is a major objective of HIV-1 cure research. In this study, we investigated the therapeutic efficacy of a vaccine consisting of adenovirus serotype 26 (Ad26) and modified vaccinia Ankara (MVA) with or without an SIV Envelope (Env) gp140 protein with alum adjuvant in combination with the TLR7 agonist vesatolimod (GS-9620) in 36 ART-suppressed, SIVmac251-infected rhesus macaques. Ad26/MVA therapeutic vaccination led to robust humoral and cellular immune responses, and the Env protein boost increased antibody responses. Following discontinuation of ART, virologic control was observed in 5/12 animals in each vaccine group, compared with 0/12 animals in the sham control group. These data demonstrate therapeutic efficacy of Ad26/MVA vaccination with vesatolimod but no clear additional benefit of adding an Env protein boost. SIV-specific cellular immune responses correlated with virologic control. Our findings show partial efficacy of therapeutic vaccination following ART discontinuation in SIV-infected rhesus macaques.